The Feminine Section and the political instrumentalization of flamenco dance during the Franco dictatorship (1940-1975) - Bárbara de las Heras Monastero; Patricia Delgado Granados (Historia Social y de la Educación, 2022)
This article analyzes the political instrumentalization of flamenco dance during the Franco dictatorship through the Feminine Section of Traditionalist Spanish Falange and the National Syndicalist Offensive Boards (hereinafter, FET and JONS). The research method used for this work is the historiographical based on a systematic study of primary sources consisting mainly of periodic, graphic and oral publications, as well as official documents of the time, in addition to the already published works that have addressed succinct Andalusian folklore during the Franco period (1940-1975). The results show a first autarchic stage, that of the forties, in which flamenco dance is instrumentalized under the myth of the unity of the homeland, for from the fifties, as part of the developmental strategy in the economic and openness in politics, flamenco becomes a weapon of political indoctrination to reinforce and symbolize the new national identity. In this way, the idea of ​​identity construction of the Spanish referent (Spanishness) generated by flamenco dance and its indoctrination mechanisms is valued.